Investigating the bouncing phase of a golf putt - Griffiths, I.; McKenzie, R.; Eley, L.; Brown, S. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
The present study describes the differences between how a ball bounces on a putting mat and a rubber surface. For each surface, thirty putts struck with desirable launch conditions were analysed by a Quintic ball roll system. Bouncing was greater and less random on the putting mat. A greater increase in ball roll in between bounces on the rubber surface is indicative of its greater coefficient of kinetic friction. It seems that the coefficient of kinetic friction may decrease with speed, heling to explain why putts that bounce are more difficult to control for distance.